Política de C&T e comunicação: patentes como instrumento de divulgação - Mazocco, Fabricio José (2014)
Innovation is in the agenda of political discussions and in the goals of public and private institutions, as it is becoming one of the main elements in the Science and Technology policies (S&T). The State makes an effort to expand an innovative environment, resulting in a social and economic development of the country. The patent is one of the best known indicatives of innovation. In the case of Brazil, public universities are among the main patent depositors. On the other hand, public communication is having more and more attention in academic and state discussions, for forecasting the need of a kind of communication which promotes citizenship and stimulates dialogue among the agents. Therefore, this work has the objective of analyzing the relation between S&T policies and communication, having the patent as divulging instrument. As empirical analysis, public and private institutions shall be analyzed as for the construction of patenting information and its destination, based on the premisses of public communication of science and the political definitions of S&T.